Invariants of finite solvable groups - Monakhov, V.; Trofimuk, A. (Algebra and Discrete Mathematics, 2012)
The article contains the results about invariants of solvable groups with given structure of Sylow subgroups and information about the nilpotent π-length of π-solvable groups. Open questions are formulated.